Die Selbstdarstellungen der Nonnen im Medinger Konvent - Toussaint, Gia (Die Hamburger Beginen bei St. Jacobi im Kontext ihrer Handschriften und Kultur, 2022)
The nuns’ pictorial self-portrayals in the prayer book MS J 29 (Hildesheim, Dombibliothek) from the Cistercian monastery of Medingen, completed in September 1478, document scenes from convent life before the introduction of the reform in 1479. Nuns are shown playing the organ and encountering the local lay community on Easter morning. Interestingly, the nuns are shown not in the traditional black and white Cistercian habit (that they almost certainly wore in reality) but in white garments reminiscent of the depictions of angels in this manuscript; thus, their special spiritual, angel-like status is highlighted. The reform, imposed from the outside to restore strict Cistercian discipline and not actually welcomed by the convent, restricted organ play, eliminated participation in lay processions, and perhaps brought the adoption of a new headdress. The prayer book’s illustrations give us a glimpse of a lost world of relative freedom.